The role of capital income for top incomes shares in Germany - Charlotte Bartels; Katharina Jenderny (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2014)
A large literature has documented top income share series based on income tax statistics using the common methodology established by Piketty (2001, 2003). The disappearance of capital income from the income tax base in many countries poses a major challenge to the comparability of these series both over time and between countries. First, we extend the existing German series including capital gains to 2010, and the series excluding capital gains to 2008. Second, we derive three homogeneous series by simulating legislative definitions of capital income prevailing in Germany between 2001 and 2010. For both simulation and the exclusion of capital gains, we employ a rich data set containing the tax files of all income taxpayers. Third, we construct a composite measure of stock dividends and interest income tax ows as a proxy for capital income missing in the data since 2009. We find that the drop in top income shares obtained from income tax statistics in the crisis year 2009 is largely attributable to the exclusion of capital income from the income tax base.
Keywords: D31; H2; J3; 330; income inequality; income distribution; top incomes; taxation; capital; gains; Germany